2017
DOI: 10.1002/ece3.2900
|View full text |Cite
|
Sign up to set email alerts
|

Resistance and resilience of root fungal communities to water limitation in a temperate agroecosystem

Abstract: Understanding crop resilience to environmental stress is critical in predicting the consequences of global climate change for agricultural systems worldwide, but to date studies addressing crop resiliency have focused primarily on plant physiological and molecular responses. Arbuscular mycorrhizal fungi (AMF) form mutualisms with many crop species, and these relationships are key in mitigating the effects of abiotic stress in many agricultural systems. However, to date there is little research examining whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 73 publications
(98 reference statements)
5
16
0
Order By: Relevance
“…The clear changes in AMF and pathogen communities in soil inocula experiencing drought indicate that soil moisture, or moisture-mediated shifts in either host plant status or nutrient availability can strongly influence fungal communities. Our results generally agree with previous studies that have shown shifts in fungal communities along precipitation gradients (Kivlin et al, 2011 ; Tedersoo et al, 2014 ; Zhang et al, 2016 ) and where soil moisture has been experimentally altered (Furze et al, 2017 ; Kaisermann et al, 2017 ; Meisner et al, 2018 ; Schmidt et al, 2018 ; She et al, 2018 ). These changes in composition may or may not result in altered fungal richness, which sometimes declines (Toberman et al, 2008 ; Gehring et al, 2017 ), show no difference (Schmidt et al, 2018 ; She et al, 2018 ), or even increase (Hawkes et al, 2011 ) with drought.…”
Section: Discussionsupporting
confidence: 92%
“…The clear changes in AMF and pathogen communities in soil inocula experiencing drought indicate that soil moisture, or moisture-mediated shifts in either host plant status or nutrient availability can strongly influence fungal communities. Our results generally agree with previous studies that have shown shifts in fungal communities along precipitation gradients (Kivlin et al, 2011 ; Tedersoo et al, 2014 ; Zhang et al, 2016 ) and where soil moisture has been experimentally altered (Furze et al, 2017 ; Kaisermann et al, 2017 ; Meisner et al, 2018 ; Schmidt et al, 2018 ; She et al, 2018 ). These changes in composition may or may not result in altered fungal richness, which sometimes declines (Toberman et al, 2008 ; Gehring et al, 2017 ), show no difference (Schmidt et al, 2018 ; She et al, 2018 ), or even increase (Hawkes et al, 2011 ) with drought.…”
Section: Discussionsupporting
confidence: 92%
“…In TBI systems, water availability controlled competition between Juglans nigra and maize for mineralized N (Jose et al 2000), while fine root dynamics may be largely controlled by climate, as suggested by the differential root elongation rates of J. nigra (Mohamed et al 2018). Under sub-optimal climatic conditions, we know that key microbial communities were more resilient in a temperate TBI system (Furze et al 2017), a Mediterranean agroforestry system (Guillot et al 2019), and a Zanthoxylum bungeanumbased intercropped system (Sun et al 2016). Relationships between root trait expression and microbial communities involved in soil C and N dynamics were reported under droughty conditions (De Vries et al 2016), but much work is needed to elucidate the interactive function of microbial-plant nutrient acquisition patterns in agroforestry systems to achieve resilience under environmental change.…”
Section: Imaging Nutrient Acquisition Structures With Non-destructivementioning
confidence: 99%
“…The root-associated microbiome often differs significantly from the surrounding soil communities, as a consequence of host plant properties [100][101][102]. Agroforestry systems can promote diversity, alter composition, and improve the resilience of root-associated fungal communities [103][104][105], and those effects may generate feedback on the surrounding soil after long-term establishment of tree enrichment. Studying further succession, as well as analysis of the root-associated communities of planted tree species, could help to predict future effects of tree diversity enrichment on the soil microbiome in monoculture plantations.…”
Section: Discussionmentioning
confidence: 99%